THE VATLY RADIO TELESCOPE - NGUYEN , VAN HIEP; VATLY team; DAO , TIEN KHOA (Nuclear Science and Technology, 2013)
A 2.6 m radio telescope, tuned on the 21 cm atomic hydrogen line, has been installed on the roof of the VATLY laboratory in Ha Noi. After a brief description of its performance, I report on measurements of the power density spectrum made over the visible part of the Milky Way disk. The data give strong evidence for differential rotation of the Galaxy with respect to the Sun and for an important clumping of molecular hydrogen in distinct clouds. The analysis of the measured Doppler spectra is used to map atomic hydrogen over the disk of the Galaxy. The result is compared with the arm structure observed at visible and infrared wavelengths.